1996
DOI: 10.1080/09540129650125533
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dentists' willingness to treat HIV-infected patients

Abstract: Access to oral health care is extremely important for those infected with HIV, because oral findings can lead to early detection and improved staging and management of HIV infection. In addition, oral lesions associated with HIV infection are often debilitating, but can be managed effectively with proper oral health care. There is ample evidence that dentists have, at times, resisted accepting HIV positive patients (PHIV+). The intent of the research project described below was to develop and test a model pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 0 publications
3
16
0
2
Order By: Relevance
“…Sources of HIV/AIDS stigma most commonly stem from fear of illness, contagion, and death, which in turn contributes to changes in practice behaviors toward PLWHA. This is supported by Sadowsky and Kunzel's 1996 model to predict dentists' willingness to treat PLWHA, which determined that perceived safety had the most predictive power . Seacat et al .…”
Section: Discussionmentioning
confidence: 83%
“…Sources of HIV/AIDS stigma most commonly stem from fear of illness, contagion, and death, which in turn contributes to changes in practice behaviors toward PLWHA. This is supported by Sadowsky and Kunzel's 1996 model to predict dentists' willingness to treat PLWHA, which determined that perceived safety had the most predictive power . Seacat et al .…”
Section: Discussionmentioning
confidence: 83%
“…Foi medida com uma escala de Guttman de quatro afirmativas, adaptada de Sadowsky & Kunzel 19 , que verificava a disposição para o atendimento a pacientes com infecção pelo HIV, na rede pú-blica de saúde, sob as seguintes circunstâncias: (1) paciente de manutenção HIV positivo assintomático; (2) paciente de manutenção HIV positivo sintomático; (3) paciente novo HIV positivo assintomático; e (4) paciente novo HIV positivo sintomático. Os respondentes deveriam responder as quatro afirmativas de acordo com opções "discordo totalmente", "discordo parcialmente", "estou em dúvida", "concordo parcialmente" e "concordo totalmente".…”
Section: Variáveis Do Estudounclassified
“…Estudos com a finalidade de determinar quais os fatores determinantes da conduta de profissionais de saúde em atender pacientes com HIV/AIDS têm sido desenvolvidos em vários países. Os principais fatores associados com a disposição para o atendimento de pacientes com HIV/AIDS, de acordo com lite-ratura revisada, são: preconceito 7,8,9 ; medo do contágio 7,8,9,10,11,12,13,14 ; atitudes frente à epidemia 8,10,14,15,16 ; conhecimento técnico sobre a infecção pelo HIV 10,17 ; percepção sobre risco ocupacional 11,18 ; experiência anterior com pacientes portadores de HIV/AIDS 2,8,13,18 ; estadiamento da infecção pelo HIV do paciente 14,15,16,19 ; idade e tempo de formado do profissional 2,8,12,17,20 ; e assalariamento no setor pú-blico 14,15,16,17 .…”
Section: Introductionunclassified
“…Few studies have attempted to understand the factors explaining the intention of dentists to provide dental care to persons with HIV π /AIDS. Among these studies, the willingness or unwillingness to treat patients with HIV π has been associ-221 ated with fear or perception of risk (6,11,12), fear of consequences for the practice if HIV π patients were seen in the clinic (6,12), past history of treating HIV π /AIDS patients (6,12), homophobia (6,12,13), extent of clinician's knowledge of AIDS (9), and perceived ethical obligation to treat HIV π / AIDS patients (6,7,12,14). However, in multivariate models that predicted the willingness of American dentists to treat HIV π /AIDS patients, Sadowsky et al (12) found that the two most important predictive variables were perceived safety in treating HIV π /AIDS patients and perceived norms of colleagues.…”
mentioning
confidence: 99%